Some Complexes and Modules Induced by Strongly FP-Injective Modules (Communications in Mathematical Research, 2025)
Let $R$ be an associative ring with identity. In this paper, we consider generalizations of Gorenstein FP-injective $R$-modules and FP-injective complexes, give the definitions and characterizations of strongly Gorenstein FP-injective $R$-modules and strongly FP-injective complexes, which are induced by strongly FP-injective modules. Then we investigate the strongly FP-injective dimension of complexes.
Keywords: Cotorsion pairs; strongly Gorenstein FP-injective modules; strongly FP-injective complexes; strongly FP-injective dimension